An analysis of drug approvals in India over past 5 years - Shaikh, Aarmin I.; Acharya, Chetankumar R.; Shah, Akash M.; Moradiya, Manan G.; Patel, Jay R.; Patel, Aayushi H.; Bhanderi, Mehul V. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Drug development is a tedious process and takes a long time for approval by regulatory authorities. With time, Indian authorities have revised rules and regulations for conducting clinical trials as well as for the marketing of drugs, impacting the number of drugs being approved. Method: The information about drug approvals from 2019–2023 was obtained from the CDSCO website. The single drug products were classified into 14 main anatomical therapeutic chemical (ATC) groups, while Fixed Dose Combinations (FDCs) were classified based on the system they act upon. Descriptive statistical analysis was done. The findings of our observational study were expressed as absolute numbers and percentages. Results: Total 362 drugs were approved. Out of these, 135 were single drug products, and the rest were FDCs. The highest & lowest number of drugs were approved in the year 2022 and 2019 respectively. Maximum single drug product approvals were seen in Category L-antineoplastic and immunomodulating agents, while maximum FDC approvals were for drugs acting on the endocrine system. Conclusion: There is a rising trend of approval for FDCs. The pattern of single drug products approval flattened over the years, coinciding with the implementation of new rules and regulations.